Inclusion body myositis: The interplay between ageing, muscle degeneration and autoimmunity. Issue 2 (June 2022) - McLeish, E.; Slater, N.; Sooda, A.; Wilson, A.; Coudert, J.D.; Lloyd, T.E.; Needham, M.
Abstract: Inclusion body myositis (IBM) is a slowly progressive muscle disease affecting ageing individuals. IBM presents with a distinctive pattern of weakness involving the quadriceps and finger flexor muscles, although other muscles including pharyngeal muscles become affected over time. Pathological hallmarks of IBM include autoimmune features, including endomysial infiltration by highly differentiated T cells, as well as degenerative features marked by intramyofibre protein aggregates organised into inclusion bodies. Despite some progress in understanding the cellular pathways involved in IBM, it remains untreatable, and the progression of the disease leads to progressive weakness, disability, wheelchair dependency and loss of independence. Therefore, there is an urgent need to improve our understanding of the underlying mechanisms and pathways involved in this disease to identify new treatment targets. Here, we discuss the current understanding of aetiopathogenesis, the interrelationship between autoimmunity and degeneration, and how ageing is a major influencer of both these features.